Krisis Limbah sebagai Isu Moral: Pemikiran Fazlur Rahman tentang Tanggung Jawab Manusia terhadap Alam - Haura Nadine Nayla Faidza; Dikriyah; Andi Rosa (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
The waste crisis in the big cities reflects not only the technical and structural failures of waste management, but also the moral and spiritual deterioration of modern society. However, the study of ethical solutions based on the thoughts of contemporary Islamic figures, especially Fazlur Rahman, is still limited, showing that there is a research gap in integrating dynamic Qur'anic ethics with today's ecological problems. This study aims to analyze Rahman's thoughts on human moral responsibility towards nature and its relevance in dealing with the waste crisis. Using a qualitative approach through literature study, this study applies Rahman's double movement method to interpret the Qur'anic text historically and contextually. The findings show that the Qur'anic ethics formulated by Rahman views nature as a divine mandate that must be maintained, so that waste management is not only a technocratic obligation, but also a form of spiritual and social responsibility. These ethics can be the basis for forming collective ecological awareness, encouraging sustainable lifestyles, and inspiring environmentally just public policies. This study concludes that the resolution of the ecological crisis requires a transformation of moral consciousness, with religion as the source of value that guides humans to act justly towards all creation.